Pragma based parallelization - Trading hardware efficiency for ease of use? - Kenter, Tobias; Plessl, Christian; Schmitz, Henning (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
One major obstacle for a wide spread FPGA usage in general-purpose computing is the development tool flow that requires much higher effort than for pure software solutions. Convey Computer promises a solution to this problem for their HC-1 platform, where the FPGAs are conﬁgured to run as a vector processor and the software source code can be annotated with pragmas that guide an automated vectorization process. We investigate this approach for a stereo matching algorithm that has abundant parallelism and a number of different computational patterns. We note that for this case study the automated vectorization in its current state doesn’t hold its productivity promise. However, we also show that using the Vector Personality can yield a signiﬁcant speedups compared to CPU implementations in two of three investigated phases of the algorithm. Those speedups don’t match custom FPGA implementations, but can come with much reduced development effort.

Hardware/Software Platform for Self-aware Compute Nodes - Happe, Markus; Agne, Andreas; Plessl, Christian; Platzner, Marco (Proceedings of the Workshop on Self-Awareness in Reconfigurable Computing Systems (SRCS))
Today's design and operation principles and methods do not scale well with future reconfigurable computing systems due to an increased complexity in system architectures and applications, run-time dynamics and corresponding requirements. Hence, novel design and operation principles and methods are needed that possibly break drastically with the static ones we have built into our systems and the fixed abstraction layers we have cherished over the last decades. Thus, we propose a HW/SW platform that collects and maintains information about its state and progress which enables the system to reason about its behavior (self-awareness) and utilizes its knowledge to effectively and autonomously adapt its behavior to changing requirements (self-expression).To enable self-awareness, our compute nodes collect information using a variety of sensors, i.e. performance counters and thermal diodes, and use internal self-awareness models that process these information. For self-awareness, on-line learning is crucial such that the node learns and continuously updates its models at run-time to react to changing conditions. To enable self-expression, we break with the classic design-time abstraction layers of hardware, operating system and software. In contrast, our system is able to vertically migrate functionalities between the layers at run-time to exploit trade-offs between abstraction and optimization.This paper presents a heterogeneous multi-core architecture, that enables self-awareness and self-expression, an operating system for our proposed hardware/software platform and a novel self-expression method.

Turning control flow graphs into function calls: Code generation for heterogeneous architectures - Barrio, Pablo; Carreras, Carlos; Sierra, Roberto; Kenter, Tobias; Plessl, Christian (Proceedings of the International Conference on High Performance Computing and Simulation (HPCS))
Heterogeneous machines are gaining momentum in the High Performance Computing field, due to the theoretical speedups and power consumption. In practice, while some applications meet the performance expectations, heterogeneous architectures still require a tremendous effort from the application developers. This work presents a code generation method to port codes into heterogeneous platforms, based on transformations of the control flow into function calls. The results show that the cost of the function-call mechanism is affordable for the tested HPC kernels. The complete toolchain, based on the LLVM compiler infrastructure, is fully automated once the sequential specification is provided.

Exploration of Ring Oscillator Design Space for Temperature Measurements on FPGAs - Rüthing, Christoph; Happe, Markus; Agne, Andreas; Plessl, Christian (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL))
While numerous publications have presented ring oscillator designs for temperature measurements a detailed study of the ring oscillator's design space is still missing. In this work, we introduce metrics for comparing the performance and area efficiency of ring oscillators and a methodology for determining these metrics. As a result, we present a systematic study of the design space for ring oscillators for a Xilinx Virtex-5 platform FPGA.

Programming and Scheduling Model for Supporting Heterogeneous Accelerators in Linux - Beisel, Tobias; Wiersema, Tobias; Plessl, Christian; Brinkmann, André (Proc. Workshop on Computer Architecture and Operating System Co-design (CAOS))
Keywords: funding-enhance

On the Feasibility and Limitations of Just-In-Time Instruction Set Extension for FPGA-based Reconfigurable Processors - Grad, Mariusz; Plessl, Christian (Int. Journal of Reconfigurable Computing (IJRC))

Consumer surveillance on web 2.0 - Sandoval, Marisol (The Internet & Surveillance)

A Framework for Semantic-Based Similarity Measures for \textdollar\textbackslashmathcalELH\textdollar -Concepts - Lehmann, Karsten; Turhan, Anni-Yasmin (Logics in Artificial Intelligence - 13th European Conference, JELIA 2012, Toulouse, France, September 26-28, 2012. Proceedings)

Role-depth Bounded Least Common Subsumers for EL+ and ELI - Ecke, Andreas; Turhan, Anni-Yasmin (Proceedings of the 2012 International Workshop on Description Logics, DL-2012, Rome, Italy, June 7-10, 2012)

Optimizations for the Role-Depth Bounded Least Common Subsumer in EL+ - Ecke, Andreas; Turhan, Anni-Yasmin (Proceedings of OWL: Experiences and Directions Workshop 2012, Heraklion, Crete, Greece, May 27-28, 2012)

Krieg als Standespflicht. Die militärische Erinnerungskultur spätmittelalterlicher Fürsten und Adliger - Prietzel, Malte (Militärische Erinnerungskulturen vom 14. bis zum 19. Jahrhundert. Träger – Medien – Deutungskonkurrenzen)

Veränderungen in der spätmittelalterlichen Kriegführung - Prietzel, Malte (Žalgiris – Tannenberg – Grunwald 1410. Krieg und Frieden im späten Mittelalter)

Schauspiele von Ehre und Tapferkeit. Zweikämpfe in Frankreich und Burgund im späten Mittelalter - Prietzel, Malte (Das Duell. Ehrenkämpfe vom Mittelalter bis zur Moderne)

Jeanne d’Arc. Das Leben einer Legende - Prietzel, Malte

Kot/Mist/Dreck - Bergmann, Claudia Dorit; Schart, Aaron (Das Wissenschaftliche Bibellexikon im Internet/ AT)

Fluch oder Segen?! Ein Zwischenruf zur Kompetenzorientierung im Religionsunterricht - Woppowa, Jan (Engagement. Zeitschrift für Erziehung und Schule)

Nauka rozumienia religii. Perspektywy edukacji interreligijnej w oparciu o świadectwa - Woppowa, Jan (KERYKS. Forum Pedagogicznoreligijne. Międzynarodowe – Międzykulturowe – Międzydyscyplinarne)

Bildung als Bewährung. Martin Bubers Beitrag zur Jugendbewegung und Erwachsenenbildung - Woppowa, Jan (HistoriscJugendforschung. Jahrbuch des Archivs der deutschen Jugendbewegung. Jugendbewegung und Erwachsenenbildung)

Religion(en) verstehen lernen. Perspektiven auf das interreligiöse Lernen an Zeugnissen - Woppowa, Jan (KERYKS. Religionspädagogisches Forum. international – interkulturell – interdisziplinär)

Lernen an Zeugnissen. Eine kompetenzorientierter Ansatz interreligiösen Lernens - Woppowa, Jan (Kirche und Schule)